Revitalisasi Akhlak Remaja: Pendekatan Pendidikan Pesantren di Masa Kini - Naelasari, Desy; An-Nahdliyah, Khumairoh; Muslihah, Hanum Amirotul (LP3M STIT Al Urwatul Wutsqo Jombang, 2024)
This study aims to describe the role of Darul Hikmah Islamic Boarding School in Developing Adolescent Morals in Jlopo Hamlet, Tebel, Bareng, Jombang. This research method uses qualitative methods with data collection techniques in the form of interviews, observation, and documentation. Data analysis was carried out using qualitative descriptive methods, and data validity testing through extended observation, increased persistence, triangulation, and friend discussions. The results showed that the morals of teenagers towards elders in Jlopo Hamlet were classified as good. They use polite language, say greetings first, and do not cut the conversation. The role of Darul Hikmah Islamic Boarding School is very significant in fostering adolescent morals. As an educational institution, this boarding school is a place to gain knowledge for teenagers. As a social institution, the boarding school involves teenagers in religious activities such as pilgrimage to the grave of the saint. As a guide, the boarding school organises recitation and mastery of the yellow book which teaches morals and fiqh. With various efforts from Darul Hikmah Islamic Boarding School, teenagers in Jlopo Hamlet are able to show good morals. This research is expected to contribute to the development of knowledge in the field of Islamic education and pesantren studies, as well as provide recommendations for other Islamic boarding schools in improving the quality of adolescent moral development